KOMPOSISI BOTANI DAN PRODUKSI HIJAUAN MAKANAN TERNAK MUSIM HUJAN PADA PADANG PENGGEMBALAAN ALAM DESA OESAO, KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Daud Ndjuka Tana; Herayanti Panca Nastiti; Stefanus Tany Temu (Universitas Nusa Cendana, 2015)
This research was conducted in the area of ​​gras land in the Oesao village, Sub- District of East Kupang , Kupang Regency. This study aims to determine and obtain data on botanical composition and forage production rain season forage on gras land, so it can support the improvement of livestock product so as to support increased productivity of livestock in the Oesao Village, Sub-District Of East Kupang, Kupang Regency. The method used in this research is the method of survey and direct measurements in the pasture. Measurement of forage production is done by using the